Pembuatan Rumah Burung Hantu sebagai Upaya Pengendalian Hama Tikus Ramah Lingkungan dan Mengurangi Ketergantungan Pestisida Kimia di Desa Pematang Kasih - Ariqah Luthfiyah; Aprilia Putri Silaen; Cut Latifah Putri; Dafa Ikhwanu Shafa; Khairunnisa Khairunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) in Pematang Kasih Village, Pantai Cermin District, focused on the construction of owl houses (RUBUHA) as an environmentally friendly effort to control rice field rats. The background to this activity was the high level of rat infestation that was detrimental to local farmers' rice harvests and the excessive use of chemical pesticides, which had the potential to negatively impact human health and ecosystem balance. The research method used was descriptive qualitative, with data collection techniques through direct observation in agricultural fields, interviews with farmer groups, and documentation of the owl house construction process. The results showed that the village community responded positively to this program because the use of owls as natural predators was proven to be more effective in controlling the rat pest population while reducing dependence on chemical pesticides. In addition, this program also increased public awareness of the importance of ecologically based pest control and preserving biodiversity. With the owl houses built around rice fields, it is hoped that a sustainable agricultural pattern can be created that supports the welfare of farmers while preserving the environment.